Davao City inter school e-marketplace with web service application - Zamora, Marjorie Ann Jagunos (2011)
This study was done to implement unified marketplace system for online product advertisement through the application of Web Services as a tool fr interconnecting two independent school information system. Each school information system provided students and faculty members t manage product posts, messages, and personal profiles. Each system had its own administrator which facilitates registration and monitoring on posting activities by user members. A separate system called the DISE marketplace was also developed as a central marketplace where data exchange on separate product post on each school information system can interconnect. This system used a Web Service application that involved the creation of Web Service Description Language (WSDL), in an XML language format, file for the two School Information systems. This file contains the description and specification of services that the system provides and requires. Only members from each School Information system are able to use the DISE marketplace since authentication of user is primarily done before using the system and the services it provides. User management on their products, messages and profile information are done only on each school information system it is registered. Data provided by the DISE marketplace are responses from the requested local database information from the two systems. Services provided by DISE marketplace basically about data retrieval only.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2011
Keywords: Web services; E-marketplace.; Web Service Description Language (WSDL); Webservice applications; Davao City Inter School E-marketplace (DISE); School information system; DISE marketplace; Information system; Electronic commerce; Electronic marketplace; Web service architecture